1986
DOI: 10.1097/00132586-198604000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Performance After Upper Abdominal Surgery. A Comparison of Pain Relief with Intercostal Blocks and Centrally Acting Analgesics

Abstract: The respiratory capacity was studied during the first 2 days postoperatively in 94 patients, aged 19 tn 75 years and undergoing surgery through an upper abdominal incision. Postoperative pain relief was randomly administered, either by intercostal block (i.c.b.) and centrally acting analgesics on demand, or by centrally acting analgesics alone. Respiratory studies comprising forced vital capacity (FVC), forced expiratory volume in one second (FEVI), peak expiratory flow rate (PEF) and analysis of arterial bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In the present study FVC and FEV 1.0 were reduced by 5556 and 59Yo, respectively, on the first postoperative day. This respiratory impairment is in accordance with reports from other comparable studies on patients who have undergone cholecystectomy through a subcostal oblique incision (1, 3). After intrapleural administration of bupivacaine FVC increased by 569, and FEV 1.0 by 46% on the first postoperative day and by 35: 4, and 51°/,, respectively, on the second day.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study FVC and FEV 1.0 were reduced by 5556 and 59Yo, respectively, on the first postoperative day. This respiratory impairment is in accordance with reports from other comparable studies on patients who have undergone cholecystectomy through a subcostal oblique incision (1, 3). After intrapleural administration of bupivacaine FVC increased by 569, and FEV 1.0 by 46% on the first postoperative day and by 35: 4, and 51°/,, respectively, on the second day.…”
Section: Discussionsupporting
confidence: 92%
“…We chose to use spirometry which requires maximum effort from the patient and, as a result, closely reflects the effects of pain and therefore analgesia on ventilatory performance. 2 The most important benefits of the interpleural infusion were associated with the lower incidence of side-effects and shorter time to flatus. Although patients in both groups received satisfactory analgesia, it was accompanied by a greater number of recurrent side-effects for patients in the pethidine group and consequently a requirement for more anti-emetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…7 After upper abdominal surgery such as cholecystectomy good analgesia is also required to avoid pulmonary complications. 2 Intercostal nerve blocks are effective, but repeated injections are uncomfortable for the patient and timeconsuming for the anaesthetist. The interpleural catheter technique employed in this study is technically simple and has been reported to be extremely effective after upper abdominal surgery in several series.…”
Section: Discussionmentioning
confidence: 99%